Government of Uttar Pradesh Planning Department Draft Annual Plan 1970-71 - Planning Commission (Planning Commission, 1969)
The rate of economic growth in U. P. has not been fast enough to show any appreciable impact on the per capita income. The rate of growth in the State income has been only just sufficient to meet the needs of the growing population. The State’s per capita income at the constant prices of 1960-61 which was Rs.246 at the end of the Second Plan was almost at the same level i.e. Rs.247 in the year 1967-68. Figures of State income for 1968-69 are not yet available but it is expected that the per capita 'income for the year will be around Rs.254. The rate of growth in the State income which was 2.28 per cent during 1960-61 to 1967-68 has been almost completely off-set by 2.21 per cent rate of growth in population. The rate of growth during the corresponding period at the all-India level was 3.14 per cent in the National income and 2.46 per cent in the population giving 0.67 per cent rate of growth in the per capita national income. The State has suffered in the past on account of lack of adequate investments. According to 1967 figures only 481 persons per lakh of population were employed in registered factories in the State as against 935 for the country. Most of the factories in the State are of small scale as the share of large and medium industries in net domestic products of manufacturing enterprises in U. P. was only 39.4 per cent as against the corresponding figure of 60.4 per cent for the country. The principal industries in the State, sugar, textile and oil, have been sick for sometime past as they suffer from lack of modernization and replacement of old machines. The general engineering and chemical industries which have recently been set up in the State are not yet able to utilise their full capacity.
Draft Annual Plan 1970-71
Government of Uttar Pradesh